Neurobiological signature of intimacy in anorexia nervosa. (21st January 2019) - Maier, Simon; Spiegelberg, Julia; van Zutphen, Linda; Zeeck, Almut; Tebartz van Elst, Ludger; Hartmann, Armin; Holovics, Lukas; Reinert, Elke; Sandholz, Angelika; Lahmann, Claas; Domschke, Katharina; Glauche, Volkmar; et al.
Abstract: Background: Intimacy and psychosexual development represent core problems of anorexia nervosa (AN). Experiential and neurobiological evidence however is scarce. Material and methods: Thirty‐one female AN patients were compared with 35 non‐patients (NP) and 22 recovered participants (REC) by using functional magnetic resonance imaging. Participants viewed pictures of couples in intimate relationships and control stimuli. Results: AN patients experienced intimate stimuli with lower valence and dominance. AN showed decreased activation of parietal cortices. NP decreased the prefrontal cortex response, which AN patients did not. REC participants did not differ from NP on a behavioural level, though with regard to the neural signature. Discussion: Parietal cortices are related to processing of erotic themes, which seems to be deficient in AN. Dysfunction of prefrontal cortices likely mirrors dysfunctional control in AN. The neural signature does not seem to be state‐related considering results of REC.